Metabolic activity of erosions in rheumatoid arthritis. Issue 3 (March 1986) - Pitt, P; Berry, H; Clarke, M; Foley, H; Barratt, J; Parsons, V
Abstract : The hands of 10 patients with rheumatoid arthritis were investigated with diphosphonate scanning and radiology. Increased uptake of isotope can be associated with some erosions but not all and also reflects other processes more linked to acute inflammatory areas unassociated with the development of erosions. If the latter are the hallmark of active rheumatoid arthritis then bone scans are not.